PERHITUNGAN KOLONI BAKTERI SUSU SEGAR PADA RUANG WARNA YCBCR - Fitri, Zilvanhisna Emka; Sahenda, Lalitya Nindita; Holili, Rexy Solehudin Abdi; Rukmi, Dyah Laksito (NERO (Networking Engineering Research Operation), 2023)
The problem with fresh milk on the SPR farm is the manual milking process, which causes the milk to be less hygienic and becomes an ideal growing medium for microbes. Therefore, it is necessary to carry out a procedure for checking the microbiological status as an indicator of food safety. To test for microbial contamination in fresh milk, namely the Total Plate Count (TPC) test, but in this study the focus is on the calculation of bacterial colonies using digital image processing techniques. The stages of the research carried out are the preprocessing process (cropping and color conversion to YCbCr space), image enhancement (addition of brightness and inverse image), the segmentation combination process (gray degree and channel area thresholding) and colony calculation using labeling based on the proximity of 8 neighbors to the feature area. From the results of the study, it was found that bacterial colonies had a wide area range of 150 ≤ area ≤ 8000. A comparison of manual TPC calculations with the system has been carried out on 5 test samples and obtained an average error difference of 0.176.Keywords : channel area thresholding, bacterial colonies, fresh milk, TPC, YCbCr